(untitled) (Rivista italiana di Paleontologia e Stratigrafia, 2004)
A review of the ammonite faunas and biostratigraphy of the uppermost Kimmeridgian - lowermost Middle Volgian of Central Russia is presented. The major role of the Sub-mediterranean ammonites in the Volgian assemblages is described, providing additional detail to the existing scheme of Tithonian-Volgian correlations. The base of the Tithonian and the base of the Volgian are coincident, based on the association of Neochetoceras steraspis-Lingulaticeras solenoides. The Klimovi Zone corresponds to most of the Hybonotum Zone. However, the top of the Hybonotum Zone, based on the distribution of Paralingulaticeras, falls within the Sokolovi Zone. The allocation of a Tenuicostata Subzone (with two horizons: neoburgense and puschi) in the Pseudoscythica Zone is proven. The neoburgense horizon may be correlated with the ciliata and penicillatum horizons of Neuburg and, probably, with the Semiforme Zone. The findings of Lingulaticeras blaschkei, Pseudolissoceras, and Sutneria in the Panderi Zone of the Middle Tithonian suggest that the base of the Middle Volgian may not be younger than the Middle Tithonian Fallauxi Zone.